2022
DOI: 10.1103/physrevb.105.214429
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of spin waves by a Bloch domain wall: Effect of the dipolar interaction

Abstract: It is known that a Bloch domain wall in an anisotropic ferromagnet is transparent to spin waves. This result is derived by approximating the dipolar interaction between magnetic moments by an effective anisotropy interaction. In this paper we study the the scattering of spin waves by a domain wall taking into account the full complexity of the dipolar interaction, treating it perturbatively in the distorted wave Born approximation. Due to the peculiarities of the dipolar interaction, the implementation of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Analytical calculations and micromagnetic simulations have indicated that in periodic magnetization textures, the nonlocal dipole field arising from the finite film thickness leads to the formation of a band structure. 30 More recently, the role of the dipolar field has been also confirmed by Laliena et al 31 In this work, the authors have shown theoretically that Bloch domain walls, which are transparent to the SWs propagation when the dipolar interaction is neglected, are able to reflect SWs if the dipolar interaction is taken into account properly.…”
Section: Introductionsupporting
confidence: 63%
“…Analytical calculations and micromagnetic simulations have indicated that in periodic magnetization textures, the nonlocal dipole field arising from the finite film thickness leads to the formation of a band structure. 30 More recently, the role of the dipolar field has been also confirmed by Laliena et al 31 In this work, the authors have shown theoretically that Bloch domain walls, which are transparent to the SWs propagation when the dipolar interaction is neglected, are able to reflect SWs if the dipolar interaction is taken into account properly.…”
Section: Introductionsupporting
confidence: 63%